Profile of spontaneous bacterial peritonitis in non-alcoholic fatty liver disease cirrhosis - Zeeshan Ahmad Wani; Mohamad Muzzafer Mir; Nissar Hussain Hamadani; Umer Amin Bhat; Waseem Imtiyaz Khuroo (Asian Journal of Medical Sciences, 2024)
Background: Etiology of chronic liver disease (CLD) has an impact on the profile of spontaneous bacterial peritonitis (SBP) in terms of infection acquisition, resistance pattern, and treatment outcome. Aims and Objectives: This study aimed to study infection acquisition, antibiotic resistance pattern, and treatment outcome in patients with non-alcoholic fatty liver disease (NAFLD) cirrhosis with SBP. Materials and Methods: This observational prospective study was carried out in Government Medical College; Srinagar: over a period of 2 years from 2017 onward. We did analysis of patients with NAFLDs cirrhosis. We studied infection acquisition, antibiotic resistance pattern, and treatment outcome in this group of patients. Results: Over 2-year period, 246 patients were enrolled. The mean age of patients was 57.09±13.90 years. Hepatitis B virus and NAFLD were the major etiological contributors to the burden of CLD amounting to 51.20% in Kashmir. SBP was present in 33/57 (57.90%) of NAFLD cirrhosis patients. Child-Turcotte-Pugh Class C was 63.60%. Patients with culture-positive SBP (CP-SBP) were 45.45%. In patients of SBP with etiology other than NAFLD, CP-SBP was 61% whereas culture-negative SBP was 38.77%. Conclusion: In our region, NAFLD is one of the leading contributors to CLD. In this study, the trend toward worse treatment outcome and mortality in the patients with NAFLD SBP was observed.